Sri Lanka, the emerald island - Devendra, Tissa; Guṇasēna, Dēvikā; Clarke, Arthur (New Delhi, India : Lustre Press : Roli Books, 1996)
Historical outline of the history of Sri Lanka.
Keywords: Sri Lanka -- History; Sri Lanka -- Pictorial works